The historical foundations of EU competition law - Patel, Kiran Klaus; Schweitzer, Heike (Oxford University Press, 2013)
A critical examination of the establishment and evolution of European competition law and policy, this volume unveils the history of European economic, and political, integration through a study of the foundations and development of its antitrust law.